DIGITAL TECHNOLOGIES - THE BASIS OF THE DEVELOPMENT OF THE INNOVATIVE ECONOMY (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
In this article, the role and importance of digital technologies in the formation of innovative economy is widely explained. Also, opinions and comments on the development of innovative economy using digital technologies were expressed. The trends in the introduction of digital technologies for the development of the innovative economy were reviewed and suggestions and recommendations were developed. The development trends of the innovative economy in the current society, the demand for digital technologies in the formation of the innovative economy are analyzed. The development of digital technologies in the Economy and social life of our country, and their advantages and disadvantages are analyzed. Based on the analysis, solutions to existing problems are given.
Keywords: Innovations; digital technologies; digital economy; Innovative economy; artificial intelligence; network efficiency; innovative technologies; economic sectors; international cooperation; institutional economy